The Effect of Talent Management and Compensation on Millenial Employee Retention in Pt. XYZ, with Employee Engagement as a Mediating Factor - Manullang, Asrini Ruth Chrysan; Andrias, Mone S. (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2023)
This study examines the impact of talent management and compensation on employee retention, with a focus on millennial employees at PT XYZ, a state-owned company in Indonesia. The objective is to understand the relationship between talent management, compensation, and employee engagement, and their combined effect on retention. This research project will utilize a quantitative methodology as the approach, aiming to gather robust numerical data from a specific demographic: currently employed millennial workers at PT XYZ. An online survey was conducted to collect data from 182 millennial employees at PT XYZ, and the collected data were subsequently analyzed using the Structural Equation Modeling (SEM) model. The analysis of the data was performed using the Lisrel application. The results show that both talent management and compensation have a significant impact on employee retention, and this relationship is further strengthened by the mediating role of employee engagement. It is important to note that compensation plays a crucial role in optimizing retention among millennial employees, as evidenced by its strong influence in this study. These findings are somewhat inconsistent with prior research, which indicates that although compensation is recognized as a contributing factor to millennial employee retention, it is not the predominant factor. The implications of this study are relevant for both theoretical advancement in the field and practical application by HR practitioners in PT XYZ, providing insights for developing effective retention strategies.